39 Investigation of Ovine DRD2. (7th December 2018) - Adams, S; Kojima, C; Britt, J; Miller, M; Koch, B; Andrae, J; Duckett, S
Abstract: Two experiments were conducted to investigate the role of a single nucoletide polymorphism (SNP) in the ovine dopamine receptor 2 (DRD2) gene and fescue toxicosis during gestation on fetal lamb weigh and growth. In experiment 1, Pregnant ewes (n=32) were divided into four treatments receiving either endophyte-free tall fescue seed (E-) or endophyte infected tall fescue seed (E+; 1772 ug ergovaline + ergovalaline/ hd/d) during MID (d 35- d85) and LATE (d 86 – d 133) gestation in a 2 X 2 factorial. Terminal surgeries were performed at d 133 of gestation and ewe liver tissues were obtained for DNA and examination of DRD2 SNPs. A SNP was identified at g270a and all ewes were genotyped (GENO; AA, AG or GG). Results of this study indicate GG ewes had heavier fetal weights as well as lower thyroid and cortisol concentrations. E+ fescue treatment during LATE gestation had reduced (P < 0.05) fetal lamb weight but there was no interaction between GENO and fescue treatment. Experiment two (n=60) was similar in design, but ewes were genotyped and then assigned to fescue treatment by genotype and lambs were tracked through weaning. Results indicate heavier lamb birth weight and crown rump lengths for GG genotypes (P < 0.05). Ewes consuming E+ fescue during LATE gestation had reduced birth and weaning weights but there was no interaction between GENO and fescue treatment. There was an interaction (P = 0.06) between GENO and fescue treatment for birth to weaning ADG. Lambs from GG ewes that were fed E+/E+ fescue had lower gains compared to other fescue treatments from GG ewes. Ewe cortisol concentration was lower (P<0.05) for GG ewes. Ewes with GG genotype for DRD2 SNP had heavier lambs at birth and weaning but postweaning growth may be hindered with fescue consumption during gestation.